Water and polypeptide conformations in the gramicidin channel. A molecular dynamics study. - Chiu, S W (1989)
Theoretical studies of ion channels address several important questions. The mechanism of ion transport, the role of water structure, the fluctuations of the protein channel itself, and the influence of structural changes are accessible from these studies. In this paper, we have carried out a 70-ps molecular dynamics simulation on a model structure of gramicidin A with channel waters. The backbone of the protein has been analyzed with respect to the orientation of the carbonyl and the amide groups. The results are in conformity with the experimental NMR data. The structure of water and the hydrogen bonding network are also investigated. It is found that the water molecules inside the channel act as a collective chain; whereas the conformation in which all the waters are oriented with the dipoles pointing along the axis of the channel is a preferred one, others are also accessed during the dynamics simulation. A collective coordinate involving the channel waters and some of the hydrogen bonding peptide partners is required to describe the transition of waters from one configuration to the other.